REPRESENTASI KAMPUNG SENI DAGO SEBAGAI OBJEK WISATA KOTA BANDUNG - Dasrun Hidayat; Alvi Fitrianti; Mahardiansyah Suhadi; Baruna Tyaswara (J-IKA, 2014)
Abstract -“Dago Art Village Imaging”. For establishment of positive image to public and attract tourists, both domestic and international, to revisit Bandung City. This research use qualitative approach and descriptive study to obtain results of Dago Art Village imaging for object of interest to tourists in Bandung City. The results of the research suggest that many people do even not yet know the existence of Dago Art Village. At the outset, the concept of Dago Art Village comprise meaning, benefit, function, and role of artist in development of Dago Art Village imaging for object of interest to tourists by means of socialization, promotion, and program. Government have important  role  in  development  of  Dago  Art  Village  including  program,  socialization,  and promotion. We concluded that, first, Dago Art Village for creative object of interest to tourists offer diverse cultural arts that about to be abandoned by young generation today; second, Artist have particularly important role in development of Dago Art Village; third, Government engage in construction of infrastructure and means programs to support Dago Art Village imaging for object of interest to tourists in Bandung City. Keyword: Attractions, Role of Government, The Role of Artists.   Abstrak  -  Pencitraan  Kampung  Seni  Dago,sebagai  pembentukan image positif kepada masyarakat luas dan menarik para wisatawan baik domestic maupun mancanegara untuk kembali mengunjungi kota Bandung. Penelitian ini menggunakan pendekatan kualitatif dengan studi deskriptif. Fokus pada pencitraan Kampung Seni Dago sebagai objek wisata kota Bandung. Hasil penelitian menunjukan bahwa masih banyak masyarakat yang belum mengetahui keberadaan kampong seni Dago. Dimulai dari konsep kampong seni Dago yang didalamnya meliputi makna, manfaat, fungsi dan peran  seniman dalam pengembangan pencitraan  sebagai  objek  wisata kampong seni Dago yaitu sosialsasi kampong seni Dago, promosi, program.Peran pemerintah pengembangan objek kampong seni Dago meliputi program, sosialisasi, danpromosi. Berdasarakan hasil dari kesimpulan pertama Kampung Seni  Dago sebagai salah satu objek wisata yang kreatif dengan menawarkan beragam seni budaya yang saat ini mulai ditinggalkan oleh generasi muda sekarang, kedua  Seniman  memberikan peranan yang sangat penting dalam perkembangan kampung seni dago, ketiga Pemerintah ikut serta dalam membangun program sarana dan prasarana untuk menunjang pencitraan kampung seni dago sebagai objekwisata kota Bandung  Kata Kunci : Objek wisata, Peran Pemerintah, Peran Seniman